Microbial Diversity in Hot Spring Soil Microbiome - Susanti, R.; Listiaji, Prasetyo; Mukaromah, Riska Laila; Nisa, Farah Fitrotun; Kenarni, Naina Rizki; Jaya, Adi Franata (Biosaintifika: Journal of Biology & Biology Education, 2025)
Hot springs are natural habitats for thermophilic and hyperthermophilic microorganisms with optimal growth temperatures. This study was conducted using a metagenomic approach to analyze the microbial communities of Nglimut hot spring soils, Mount Ungaran. This study used an exploratory observational method. A total of ten samples of hot spring sediment soil were taken purposively in Nglimut hot spring, Mount Ungaran. A total of 600 grams of hot spring sediment soil samples were used for chemical analysis and 50 grams of samples for metagenomic analysis based on 16S rRNA V3-V4 gene marker regions. The total microbiota sequences analyzed in this study were 103,889 OTUs, consisting of 98,603 Bacteria OTUs and 5,286 Archaea OTUs. At the phylum level, all DNA sequences of soil microbiota bacteria identified 53 phyla, dominated by Proteobacteria (19.42%), Chloroflexi (17.21%), Nitrospirota (13.76%), Bacteroidota (7.67%) and Firmicutes (7.33%). At the order level, 305 bacterial orders were found, dominated by Nitrospirales (12.35%), Burkholderiales (7.99%), Rhizobiales (5.77%), Ignavibacteriales (4.06), and Anaerolineales (3.92%). A total of nine archaea phyla were identified in the hot spring soil, dominated by Crenarchaeota (85.13%), Nanoarchaeota (7.13%) and Halobacterota (5.58%). At the order level, 15 archaea orders were identified, dominated by Nitrosopumilales (64.08%), Nitrososphaerales (14.39%), Woesearchaeales (7.24%), Bathyarchaeia (6.15%), and Methanosarciniales (5.07%). The bacteria that dominate the soil of hot springs are bacteria that can survive at high temperatures (thermophilic) and are able to utilize sulfur. The presence of archaea in hot spring soils helps increase the activity of sulfate-reducing bacteria in sulfur-containing soils.